Disrupting self-evaluative processing with electrostimulation mapping during awake brain surgery - Ng, Sam (Sci Rep, 2021)
Brain awake surgery with cognitive monitoring for tumor removal has become a standard of treatment for functional purpose. Yet, little attention has been given to patients’ interpretation and awareness of their own responses to selected cognitive tasks during direct electrostimulation (DES). We aim to report disruptions of self-evaluative processing evoked by DES during awake surgery. We further investigate cortico-subcortical structures involved in self-assessment process and report the use of an intraoperative self-assessment tool, the self-confidence index (SCI). Seventy-two patients who had undergone awake brain tumor resections were selected. Inclusion criteria were the occurrence of a DES-induced disruption of an ongoing task followed by patient’s failure to remember or criticize these impairments, or a dissociation between patient’s responses to an ongoing task and patient’s SCI. Disruptions of self-evaluation were frequently associated with semantic disorders and critical sites were mostly found along the left/right ventral semantic streams. Disconnectome analyses generated from a tractography-based atlas confirmed the high probability of the inferior fronto-occipital fasciculus to be transitory ‘disconnected’. These findings suggest that white matters pathways belonging to the ventral semantic stream may be critically involved in human self-evaluative processing. Finally, the authors discuss the implementation of the SCI task during multimodal intraoperative monitoring.